2022
DOI: 10.24875/j.gamo.m18000158
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from cancer in Mexico: 2015 update

Abstract: Introduction: Cancer is one of the leading causes of mortality in México and is expected to rise in the next years mostly because of an aging population. Nevertheless, only a few comprehensive studies of cancer mortality have been published recently. Objective: Provide an update of the cancer mortality in México. Material y methods: We analyzed official death certification using data-base from Instituto Nacional Estadística y Geografía (INEGI) and population trends from Consejo Nacional de Población (CONAPO). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
0
9
0
7
Order By: Relevance
“…According to data from GLOBOCAN, 190,667 incident cancer cases occur in Mexico every year, among which 7811 correspond to LC cases, with a standardized rate of 5.8. 1 In terms of mortality, a total of 33,781 deaths due to LC occurred in Mexico from 2012 to 2016. In 2016 alone, 7044 deaths were attributable to LC, making this the highest-mortality neoplastic disease in Mexico; further, LC is a sub-diagnosed disease, and therefore this figure might be higher.…”
Section: Lc Epidemiology In Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…According to data from GLOBOCAN, 190,667 incident cancer cases occur in Mexico every year, among which 7811 correspond to LC cases, with a standardized rate of 5.8. 1 In terms of mortality, a total of 33,781 deaths due to LC occurred in Mexico from 2012 to 2016. In 2016 alone, 7044 deaths were attributable to LC, making this the highest-mortality neoplastic disease in Mexico; further, LC is a sub-diagnosed disease, and therefore this figure might be higher.…”
Section: Lc Epidemiology In Mexicomentioning
confidence: 99%
“…Mexican women tend to have a disease presentation at an earlier age, with a median of 59 years of age at diagnosis. 1…”
Section: Lc Epidemiology In Mexicomentioning
confidence: 99%
“…Thus, breast cancer (BC) (C50) recorded 6,854 deaths 2 , i.e. an increase of 8% (n = 550) in comparison with 2015 4 , mainly in women aged > 45 years, and it outranked others, such as cervical cancer 2 , which had already been reported since 2006 5 . Moreover, according to BC mortality estimates, a continuous increase in women aged > 25 years is expected for the next few years 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In view of this scenario, it has been suggested that the lack of an organized screening program 6 , capable of performing sufficient mammograms in the target population, of providing adequate diagnosis and treatment, as established by the NOM-041-SSA2-2011 standard for the prevention, diagnosis, treatment, control and epidemiological surveillance of BC 7 , could partially explain the magnitude of BC-related mortality in Mexico 5 , which has been recently documented [2][3][4] . In the USA, for example, the mortality decrease over several years has been associated, in part, with the implementation of early detection strategies using mammography, together with advances in medical treatments 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, cervical cancer is still a major cause of death from malignant neoplasms. [ 4 ] This cancer has different screening methods; nevertheless, the Pap smear is widely accepted by the Mexican women. [ 5 ] In addition, during the interview for cytology collection, it is systematically asked if there is a smoking habit.…”
mentioning
confidence: 99%